2020
DOI: 10.1007/s11240-020-01937-9
|View full text |Cite
|
Sign up to set email alerts
|

Temporary immersion systems to improve alder micropropagation

Abstract: A protocol has been developed for the propagation of Alnus glutinosa axillary shoots in liquid medium. The explants were cultured in Woody Plant Medium supplemented with 0.1 mg l − 1 benzyladenine and 0.5 mg l − 1 indole acetic acid. The effect of the bioreactor type (RITA® and Plantform™), frequency of the immersions, regulator concentrations, and volume of medium per explant was investigated. All the treatments with the temporal immersion systems (TIS) increased the proliferation rates. The best results were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 57 publications
1
12
0
Order By: Relevance
“…The multiplication of both clones was more efficient in bioreactors than in jars with semisolid medium. Similar results have been reported for other woody plants such as calabash tree [39], eucalyptus [40], apple [41], teak [42,43], pistachio [44], chestnut [45], hazelnut [46], yerba mate [47], willow [48], olive [49], alder [50] and pear [51].…”
Section: Discussionsupporting
confidence: 87%
“…The multiplication of both clones was more efficient in bioreactors than in jars with semisolid medium. Similar results have been reported for other woody plants such as calabash tree [39], eucalyptus [40], apple [41], teak [42,43], pistachio [44], chestnut [45], hazelnut [46], yerba mate [47], willow [48], olive [49], alder [50] and pear [51].…”
Section: Discussionsupporting
confidence: 87%
“…Similar growth and multiplication coefficients were observed in both bioreactors, although a slight increase of hyperhydricity was detected in Plantform™. In our previous studies on chestnut (Vidal et al, 2015 ), willow (Regueira et al, 2018 ), and alder (San José et al, 2020 ), we observed minimal hyperhydricity in those bioreactors, and the shoots showed significantly increased shoot length and multiplication coefficient than those cultured in RITA® vessels. In those experiments, Plantform™ vessels received additional aerations of 1 min every hour, whereas in this study, no additional aeration was applied to cannabis explants.…”
Section: Discussionmentioning
confidence: 57%
“…These systems have been successfully used for micropropagation of Stevia rebaudiana (Melviana et al, 2021), Colocasia esculenta L. Schott (Mancilla-Álvarez et al, 2021), Agave angustifolia (Monja-Mio et al, 2021), Rosmarinus officinalis L. (Villegas-Sánchez et al, 2021), Dracocephalum forrestii (Weremczuk-Jezyna et al, 2020), Guarianthe skinneri (Leyva-Ovalle et al, 2020), and the number is increasing steadily. In our laboratory, we have developed protocols using bioreactor propagation systems with liquid medium for axillary shoots of chestnut, alder and willow (Vidal et al, 2015;Cuenca et al, 2017;Regueira et al, 2018;San José et al, 2020;Gago et al, 2021), and somatic embryos of Quercus robur (Mallón et al, 2012(Mallón et al, , 2013. Some micropropagation protocols have been developed for C. sativa (Adhikary et al, 2021;Hesami et al, 2021a;Monthony et al, 2021b).…”
Section: Introductionmentioning
confidence: 99%
“…In the liquid cultures are used with palm plant, while the somatic embryo formation was observed in 52% of the callus using 2,4-D [56], the reproduction coefficient of 5.97 shoots per explant was reported in the redbud plant [57]. In a study using a bioreactor, it was observed that the alder plant formed axillary shoots in a WPM environment enriched with 0.1 mg/L BAP and 0.5 mg/L IAA [58]. No positive results were obtained in the experiments where we used different cytokines (BAP and KIN) and auxin (IAA) hormones together or separately.…”
Section: Discussionmentioning
confidence: 99%